Automation of subjective measurements of speech intelligibility in analogue telecommunication channels - BRACHMAŃSKI, Stefan (Archives of Acoustics, 2008)
A method of evaluation of speech transmission quality, called "modified intelligibility test with forced choice" (MIT-FC), is presented. This method provides a~fully automated measurement of speech intelligibility (the listener's task is to select on the computer monitor which of the alternative utterances presented visually to him was spoken). The MIT-FC method was implemented in a stationary version for measurements of telecommunication systems and chains and in a portable version for the measurements of auditoria and mobile communication systems. The results of application of the MIT-FC method in telecommunications have been presented and the results obtained have been compared with those of traditional intelligibility tests.